Within‐population variation in body size plasticity in response to combined nutritional and thermal stress is partially independent from variation in development time. (8th October 2022) - Chakraborty, Avishikta; Walter, Greg M.; Monro, Keyne; Alves, André N.; Mirth, Christen K.; Sgrò, Carla M.
Abstract: Ongoing climate change has forced animals to face changing thermal and nutritional environments. Animals can adjust to such combinations of stressors via plasticity. Body size is a key trait influencing organismal fitness, and plasticity in this trait in response to nutritional and thermal conditions varies among genetically diverse, locally adapted populations. The standing genetic variation within a population can also influence the extent of body size plasticity. We generated near‐isogenic lines from a newly collected population of Drosophila melanogaster at the mid‐point of east coast Australia and assayed body size for all lines in combinations of thermal and nutritional stress. We found that isogenic lines showed distinct underlying patterns of body size plasticity in response to temperature and nutrition that were often different from the overall population response. We then tested whether plasticity in development time could explain, and therefore regulate, variation in body size to these combinations of environmental conditions. We selected five genotypes that showed the greatest variation in response to combined thermal and nutritional stress and assessed the correlation between response of developmental time and body size. While we found significant genetic variation in development time plasticity, it was a poor predictor of body size among genotypes. Our results therefore suggest that multiple developmental pathways could generate genetic variation in body size plasticity. Our study emphasizes the need to better understand genetic variation in plasticity within a population, which will help determine the potential for populations to adapt to ongoing environmental change. Abstract : We show that within‐population level body size plasticity in response to combinations of temperature and nutrition is distinct from mean population level plastic response. This means that different genotypes within a population vary in the extent of nutritional plasticity of wing size depending on their rearing temperature (25ºC vs 28ºC). We sought to understand the developmental basis for this genetic variation in body size plasticity. Since body size is the final product of growth rate and the time an animal spends growing, we assessed whether egg to adult development time could predict wing size plasticity. We selected genotypes that showed high or low plasticity in response to combinations of diet and temperature and tested the correlation between the response of developmental time and body size. We found genetic variation in development time plasticity was poorly correlated with body size plasticity. Therefore, this suggests that genetic variation in body size plasticity to combinations of environmental conditions is achieved through multiple developmental processes.